BERDAMAI DENGAN SYARIâAT - ., Addiarrahman (Islamic University of Indonesia, 2010)
The desire to form the state base on islamic law (read; formalization of islamic law) which is sound-back post reformation era, create Muslim-Christian relation or with non-Muslim in generally have been convulsively. Every religion group, had been hidding the feeling threatened (perasaan terancam) that was colonial heritage. This is more sensitive and make the conflict among them frequently. Deservedly, antagonistic discourse must be avoid and deep communication very important to make religious live more tolerant, harmonious, and peaceful. This is vary difficult if we not begin with revealed the moment of history that had a long time been making the collective memory those feeling threatened. By these reason, this writings made one. Keywords: formalization of Islamic Law, muslim-christian relation, feeling threatened, collective memory